Implementation of Inclusive Education for Deafblind Students: A Systematic Literature Review of Challenges and Best Practices - Weningsih Weningsih; Ahsan Romadlon Junaidi; Ranti Novianti; Wiwik Dwi Hastuti (Universitas Negeri Malang, 2025)
Inclusive education for students with deafblindness continues to face major challenges, particularly in developing countries, due to limited policies, a lack of trained educators, and scarce resources. This study aims to identify both the challenges and best practices in implementing inclusive education for students with deafblindness through a Systematic Literature Review (SLR) approach. The findings reveal that successful inclusion depends on teacher preparedness, the use of assistive technology, and supportive educational policies. Developed countries have implemented strategies such as communication interveners and multisensory learning methods, while developing nations struggle with resource limitations and low public awareness. This study emphasizes the importance of family involvement, adapting the learning environment, and collaboration among schools, communities, and governments to support effective inclusion. As a recommendation, enhancing teacher training, providing assistive technology, and evidence-based policymaking are crucial to improve accessibility and the quality of education for students with deafblindness.